2023
DOI: 10.3390/futurepharmacol3030039
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammasome Biomarkers as Predictors of Diabetic Retinopathy Progression: Evidence from a Pilot Study

Charisse Y.-J. Kuo,
Ilva D. Rupenthal,
Michael Booth
et al.

Abstract: The nucleotide-binding oligomerization domain (NOD)-like receptor (NLR) protein 3 (NLRP3) inflammasome pathway is believed to mediate chronic inflammation in diabetic retinopathy (DR); however, its impact on the progression of DR remains to be elucidated. Therefore, the primary aim of this pilot study was to determine whether systemic inflammasome biomarkers interleukin (IL)-1β and IL-18 can be used to predict DR progression. DR screening results were analyzed against weight, level of glycated hemoglobin (HbA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…A systematic literature review showed that DR progression correlates with increasing levels of inflammasome biomarkers in both the vitreous and serum, suggesting serum inflammasome levels can potentially be used to predict DR progression [42]. Moreover, a clinical pilot study showed that in a cohort of patients who have undergone bariatric surgery, the group that progressed in DR 1 year post-surgery had a significant increase in serum IL-18, one of the activated inflammasome biomarkers, compared to those who regressed or remained stable [43]. Collectively, these studies strongly suggest that the NLRP3 inflammasome becomes increasingly activated as DR becomes more severe.…”
Section: Clinical Evidence Of the Nlrp3 Inflammasome In Dr Progressionmentioning
confidence: 99%
“…A systematic literature review showed that DR progression correlates with increasing levels of inflammasome biomarkers in both the vitreous and serum, suggesting serum inflammasome levels can potentially be used to predict DR progression [42]. Moreover, a clinical pilot study showed that in a cohort of patients who have undergone bariatric surgery, the group that progressed in DR 1 year post-surgery had a significant increase in serum IL-18, one of the activated inflammasome biomarkers, compared to those who regressed or remained stable [43]. Collectively, these studies strongly suggest that the NLRP3 inflammasome becomes increasingly activated as DR becomes more severe.…”
Section: Clinical Evidence Of the Nlrp3 Inflammasome In Dr Progressionmentioning
confidence: 99%